2016
DOI: 10.1590/0104-07072016002920014
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Occupational Stressors and Coping Strategies in Nursing Technicians

Abstract: This is a quantitative, descriptive and exploratory research, with cross-sectional design that investigated the stressors experienced by nursing technicians working in general hospital and identified the coping strategies most used by them. The sample contained 310 participants. A sociodemographic questionnaire and the Ways of Coping Scale were used. For the analysis we used descriptive statistics and calculated the Cronbach's alpha. 60% of professionals used the strategies focused on the problem; 57.4% attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
2
9
0
4
Order By: Relevance
“…Having few resources was associated with a lack of staff disengagement (30,32) . The lack of resources in situations of high demands contributes to the increased exhaustion of health professionals (33)(34) . Lean management method, adopted in some hospitals, apparently had a positive impact on patient care satisfaction (17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…Having few resources was associated with a lack of staff disengagement (30,32) . The lack of resources in situations of high demands contributes to the increased exhaustion of health professionals (33)(34) . Lean management method, adopted in some hospitals, apparently had a positive impact on patient care satisfaction (17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest prevalence was found in the nursing assistant/technician categories. Research on the stressors experienced by nursing technicians evidenced their association with working conditions, relationships in the working environment and lack of work reward, such as low wages, disrespect, lack of incentive and recognition for the work done (31) .…”
Section: Discussionmentioning
confidence: 99%
“…As a psychophysical state, it elaborates reactions capable of provoking actions that would not be normally possible. Fear is constitutive of emotion (8) .…”
Section: [] What Worries the Most Is Not Me But The Family []mentioning
confidence: 99%
“…It is necessary to be attentive to the emotions involved, from the perspective of those who are not a part of this reality, since questions about vulnerability are raised that do not only address physical or mental characteristics, but also integrate emotions and the limits to which a person is exposed (8) .…”
Section: [] What Worries the Most Is Not Me But The Family []mentioning
confidence: 99%